Human Papillomavirus-Associated Lymphoepithelioma-Like Carcinoma of the Anal Canal: A Case Report and Literature Review - Weng, Weiwei; Sheng, Weiqi; Wang, Lei (Frontiers in Medicine, 2021)
Lymphoepithelioma-like carcinoma is a rare type of tumor that is histologically identical to lymphoepithelial carcinoma of the nasopharynx. Lymphoepithelioma-like carcinomas (LELCs) are closely associated with viral infections. Human papillomavirus (HPV)-associated LELCs have been reported in a variety of anatomic sites. We reported an extremely rare case of a 25-year-old woman with LELC derived from the anal canal, which is the second case reported at this site. The tumor was diffusely positive for p16 staining, and was correlated with high-risk HPV-16; Epstein-Barr virus-encoded small RNA was negative; PD-L1 positivity and abundant CD8+ T cell infiltration were observed, indicating a “hot” immune microenvironment. In reporting this case, we highlight the potential for misdiagnosis and suggested an association of HPV infection with LELC in the anal canal.